Shelf-life Evaluation of Packaged Fermented Cassava Flour - Dianika Lestari; Yessica Liandro; Elvina Ang; M.T.A. Penia Kresnowati (Institute for Research and Community Services, Institut Teknologi Bandung, 2019)
Cassava is a carbohydrate source with high productivity per hectare of plantation. Cassava is made into flour to extend its shelf life. However, traditional flour still has low quality due to its yellowish color and distinct odor. Fermented cassava flour (FERCAF) is produced by fermentation of cassava chips in a circulated retting fermenter by using a combination of Lactobacillus plantarum, Bacillus subtilis, and Aspergillus oryzae, followed by drying and milling. This process has been used successfully to produce flour with a white color and a neutral aroma. To enable industrial scale production and market introduction, the quality deterioration and shelf life of packaged FERCAF should be determined. The objective of this research was to investigate the effect of storage time and packaging type on the physicochemical properties and to determine shelf life of packaged FERCAF. FERCAF was stored in a controlled-incubator over 94 days using two packaging types: LDPE plastic and kraft paper. Based on the result, the number of microorganisms over 94 days of storage was within safe limits. The average estimated shelf life of packaged FERCAF was in the range of 3-4 months at ambient temperature. The shelf life of FERCAF packaged in LDPE plastic was approximately 15 days longer than that packaged in kraft paper.